Congenital hyperinsulinism in the Ukraine: a 10-year national study - Globa, Evgenia; Christesen, Henrik Thybo; Mortensen, Michael Bau; Houghton, Jayne A. L.; Nielsen, Anne Lerberg; Detlefsen, Sönke; Flanagan, Sarah E. (Frontiers in Endocrinology, 2024)
Introduction: Congenital Hyperinsulinism (CHI) has not been previously studied in Ukraine. We therefore aimed to elucidate the genetics, clinical phenotype, histological subtype, treatment and long-term outcomes of Ukrainian patients with CHI.Methods: Forty-one patients with CHI were recruited to the Ukrainian national registry between the years 2014-2023. Genetic testing (n=40), 18F-fluorodihydroxyphenylalanin and 68Ga-DOTANOC PET/CT imaging followed by surgical treatment and subsequent histological analysis (n=19) was performed through international collaboration.Results: Pathogenic variants were identified in 19/22 (86.3%) individuals with persistent CHI (p-CHI) and 8/18 (44.4%) with early remission CHI (er-CHI). Pathogenic variants in the K-ATP channel genes were the only identified genetic cause of p-CHI (ABCC8 (n=17) and KCNJ11 (n=2)) with greater genetic heterogeneity observed in those with er-CHI (ABCC8 (n=3), KMT2D (Kabuki Syndrome, n=1), Beckwith-Wiedemann syndrome (n=2) and INSR (Donohue syndrome (n=2)). Histological analysis performed on 19 children with persistent CHI confirmed focal disease in 14 (73.7%), diffuse disease in two (10.5%) and atypical histology in three (15.8%). After surgery, complete recovery was observed in all 14 with focal disease, while relapse occurred in three patients with diffuse or atypical histology.A genetic diagnosis was achieved for 67.5% (27/40) of the cohort with a higher pickup rate observed in those with p-CHI. The genetics and imaging studies enabled subtype-targeted treatment with surgical cure achieved in all individuals with focal disease.